2009
DOI: 10.1007/s10570-009-9354-5
|View full text |Cite
|
Sign up to set email alerts
|

Computation of stacking and twin faults in varieties of cotton fibers using whole powder pattern fitting technique

Abstract: The extent of stacking and twin faults has been estimated in different varieties of cotton fibers grown in the Karnataka State of India using wide-angle X-ray scattering (WAXS) data. Further, the microstructural parameters such as crystal size hNi and lattice strain (g in %) have been determined by a whole powder pattern fitting technique developed by us. In all these cases we note that the stacking and twin faults are quite significant in determining the properties of cotton fibers and their microstructural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Point defects such as broken chains, which can be characterized with a Burger’s vector, are also likely to exist. A layer slip defect is termed a stack fault, and these types of faults can shift peak locations in diffraction patterns. ,, Stack faults explain the observation of cellulose Iα and Iβ coexistence along the length of single microfibrils, as this difference in layer packing is the essential difference between cellulose Iα and Iβ . The energy required for twisting an inelastic sheet is proportional to the fourth power of the sheet diameter, meaning twist in cellulose is much more likely to be observed in small-diameter microfibrils than in large-diameter microfibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Point defects such as broken chains, which can be characterized with a Burger’s vector, are also likely to exist. A layer slip defect is termed a stack fault, and these types of faults can shift peak locations in diffraction patterns. ,, Stack faults explain the observation of cellulose Iα and Iβ coexistence along the length of single microfibrils, as this difference in layer packing is the essential difference between cellulose Iα and Iβ . The energy required for twisting an inelastic sheet is proportional to the fourth power of the sheet diameter, meaning twist in cellulose is much more likely to be observed in small-diameter microfibrils than in large-diameter microfibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a number of studies on the crystal and molecular structure of the conventional cotton fibres are being extensively studied and reported by various authors (Abhishek et al 2005;Divakara, Niranjana, & Somashekar, 2009;Samir & Somashekar, 2007a, 2007bSamir, Gopala, & Somashekar, 2007;Samir, Madhu, & Somashekar, 2010). However, we observe that similar studies on the organic cotton fibres are not reported.…”
Section: Introductionmentioning
confidence: 99%